Arterial Resection in Pancreatic Cancer Surgery: Effective After a Learning Curve. Issue 4 (12th April 2022) - Loos, Martin; Kester, Tobias; Klaiber, Ulla; Mihaljevic, André L.; Mehrabi, Arianeb; Müller-Stich, Beat M.; Diener, Markus K.; Schneider, Martin A.; Berchtold, Christoph; Hinz, Ulf; Feisst, Manuel; Strobel, Oliver; et al.
Abstract : Objective: To investigate the perioperative and oncologic long-term outcomes of patients with LAPC after surgical resection at a high-volume center for pancreatic surgery. Background: The role of surgery in LAPC with arterial involvement is controversial. Methods: We analyzed 385 consecutive patients undergoing PAR (n = 195) or PAD (n = 190) of the encased artery for LAPC between January 1, 2003 and April 30, 2019. Results: There were 183 total pancreatectomies, 113 partial pancreatoduodenectomies, 79 distal pancreatectomies, and 10 resections for tumor recurrences, including 121 multivisceral resections and 171 venous resections. Forty-three patients (11.4%) had resectable oligometastatic disease. All of the 190 patients undergoing PAD (100%) and 95 of the 195 patients undergoing PAR (48.7%) received neoadjuvant chemotherapy. The R0 (circumferential resection margin negative) resection rate was 28%. The median hospital stay was 15 days (range: 3–236). The median survival after surgery for LAPC was 20.1 months and the overall 5-year survival rate 12.5%. In-hospital mortality was 8.8% for the entire patient cohort (n = 385). With increasing case load and growing expertise, there was a significant reduction of in-hospital mortality to 4.8% (n = 186) after 2013 ( P = 0.005). The learning curve of experienced pancreatic surgeons for PAR was 15 such procedures. Conclusion: Our data demonstrate that an arterial surgical approach is effective in LAPC with promising long-term survival. PAD after neoadjuvant treatment is safe. PAR is a technically demanding procedure and requires a high level of expertise.